2015
DOI: 10.1111/jop.12314
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lin28B expression is correlated with lymph node metastasis in oral squamous cell carcinomas

Abstract: Lin28B may be a useful biomarker and novel molecular target for LN metastasis OSCC patients' treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…LIN28B protein was found to be elevated in colon tumors, and its overexpression correlated with decreased patient survival and increased tumor recurrence . Further studies also found that the overexpression of LIN28B was associated with poor prognosis in head and neck cancer, gastric cancer, oral squamous cell carcinoma patients, breast cancer, ovarian cancer, and neuroblastoma . In cases of pediatric cancers, such as germ cell tumors, neuroblastoma and WT, LIN28B appears to prolong the embryonic patterns of tissue growth .…”
Section: Discussionmentioning
confidence: 92%
“…LIN28B protein was found to be elevated in colon tumors, and its overexpression correlated with decreased patient survival and increased tumor recurrence . Further studies also found that the overexpression of LIN28B was associated with poor prognosis in head and neck cancer, gastric cancer, oral squamous cell carcinoma patients, breast cancer, ovarian cancer, and neuroblastoma . In cases of pediatric cancers, such as germ cell tumors, neuroblastoma and WT, LIN28B appears to prolong the embryonic patterns of tissue growth .…”
Section: Discussionmentioning
confidence: 92%
“…We reasoned that this discrepancy might be due to inherent tumor heterogeneity and different immunohistochemical scores and patient stratification. Interestingly, when the manuscript was in preparation, Lin and his colleague reported that elevated LIN28B correlated with lymph node metastasis in OSCC, although the mRNA abundance of LIN28B was utilized as readout by quantitative real-time PCR assay in 20 paired samples [ 32 ]. Therefore, our findings together with others strongly support the notion that LIN28B is aberrantly overexpressed in OSCC and significantly correlated with malignant clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues were microscopically screened to have >70% of their areas occupied by tumor cells; The remaining specimen (tumor, normal counterpart, and lymph node metastatic lesions) were snap frozen in liquid nitrogen and stored at −80°C for HOTAIR analysis. Six OSCC cell lines, including Fadu (hypopharyngeal squamous cell carcinoma carcinoma) [ 50 ], OECM-1 (gingival squamous cell carcinoma cells) [ 51 ], GNM (neck metastasis of gingival carcinoma) [ 52 ], Ca9-22 (gingival carcinoma) [ 53 ], SCC4 (tongue squamous cell carcinoma), HSC3 (tongue squamous cell carcinoma) cells [ 53 ] and primary normal human oral keratinocytes (NHOK) cells have been reported and were used in this study [ 5 ]. Briefly, Fadu and OECM-1 cells were in RPMI supplemented with 10% fetal bovine serum (FBS; Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%